ADYGHE (CIRCASSIAN) DIASPORA IN THE POLITICAL AND SOCIOCULTURAL SPACE OF THE NEAR AND MIDDLE EAST: TO THE ISSUE OF IMMANENT POLITICAL CONFORMISM - Kudaeva, Svetlana Grigor'evna (History, Archeology and Ethnography of the Caucasus, 2022)
Currently, the North-Caucasian diaspora consists mainly of Adyghe people (Circassians) and, according to unofficial data, numbers from 3 to 5 million people; at the same time, their number in their historical homeland slightly exceeds 700,000 people. Such state of the Adyghe ethic group was the result of events of the Caucasian War, when most of its population had to flee from their historical land and settle in the countries of the Near and Middle East. Naturally, a historical phenomenon of this magnitude could not but attract interest from the scientific community. To date, we possess enough works on the theory of diasporas, based on the experience of studying Jewish diaspora. This makes it possible to single out key criteria, typical for “classical” (historical) diasporas and extrapolate them on the Adyghe dispersion. The present paper studies one such criteria – immanent political conformism, i.e. a specific attitude of a diaspora to the political system of the country of residence, the opportunity to be productive within the receptive state. This process can be considered in the dynamics, which allows to trace the transformation of the status of the Adyghe community on different stages in connection with the fluctuations of the socio-political situation in the countries of their new residence. The specificity of the issue under question has led to the use of a wide range of methods and principles of historical research. These are retrospective, systematic and problem-chronological methods, which, coupled with the principles of historicism and objectivity, allowed for reconstruction of a full picture of the past and present in the context of interrelations and interdependence. During our study, we have come to a well-grounded conclusion that Adyghe people (Circassians) today represent high-status, integrated groups within the countries of their residence.
Keywords: Russia; Ottoman Empire; Caucasian War; Adyghe (Circassians); diaspora; immanent political conformism